Dinâmicas da Personagem: Colóquio Internacional "Figuras da Ficção 5 - Carlos Reis (Investigação, 2020)
This work brings together the production of researchers integrated in the project "Figures of Fiction", as well as other papers on the theme of this issue: "Dynamics of the Character". This theme focus on reflections on the transliterary vitality of the character and the movements of refiguration that it motivates. Therefore, the work concerns the literature, in several times and narrative genres, the cinema, the arts, the television, the publicity, the media speeches and the videogames, stressing the dynamism of the character, as a key category of the narrative